Modal Penyertaan dan Pertanggungjawaban Koperasi Panca Prima Terhadap Wanprestasi yang Dilakukan - Selajar, Sophian; Bachri, Rifkiyati; N, Nabila (Faculty of Law, Khairun University, 2018)
A cooperative is a business entity that requires capital. Cooperative capital consists of own capital and loan capital, but to develop its business, cooperatives can also conduct equity investment activities. This capital investment activity attracts the attention of the community because of its nature that bears the risk of loss but the investor is not given the authority to participate in managing the capital opening opportunities for misuse of capital investment management in cooperatives that can lead to defaults by cooperatives due to default on investors, as well as with investors. Panca Prima Cooperative which defaults on the venture capital cooperation agreement (investment capital). Thus, a problem arises whether the Panca Prima Cooperative can be held accountable for default on the venture capital cooperation agreement (equity participation) that is carried out and whether the management of the Panca Prima Cooperative is also responsible for the default carried out by the cooperative. To answer these problems normative research methods are used. Thus, it was concluded that the Panca Prima Cooperative could be held accountable for the default of the cooperative working agreement (capital participation) because the status of the Panca Prima Cooperative was a legal entity and that the Panca Prima Cooperative Management could not be held liable for defaults made by the cooperative Koperasi Panca Prima is a legal entity